Semantic Data Ingestion for Big Data Value-Driven Intelligent Analytics - Brennan, Rob; Debattista, Jeremy; Attard, Judie (IEEE, 2018)
In this position paper we describe a conceptualmodel for intelligent Big Data analytics based on both semanticand machine learning AI techniques (called AI ensembles). Theseprocesses are linked to business outcomes by explicitly modellingdata value and using semantic technologies as the underlyingmode for communication between the diverse processes andorganisations creating AI ensembles. Furthermore, we showhow data governance can direct and enhance these ensemblesby providing recommendations and insights that to ensure theoutput generated produces the highest possible value for theorganisation.
4th International Conference on Big Data Innovations and Applications
Keywords: AI ensembles; Intelligent analytics; Semantics; Data governance; Digital Engagement; Telecommunications; SEMANTIC WEB; Communication